International organizations amid global crises: analysing role selection and impact through role theory - Panke, Diana; Friedrichs, Gordon (Bristol University Press, 2024)
International Organizations (IOs) have been at the forefront of responding to crises in the 21st century, and yet there is little comparative research on how, and how effectively, they have done this. This book fills this gap by exploring what roles IOs take in response to global crises and to what effect. Bringing together a range of international contributors, the book examines a vast array of international and regional organizations, including the International Organization for Migration, World Health Organization, African Union and European Union. Aiming to answer key questions about IO behaviour, the book investigates these IOs' responses to pressing issues including the global COVID-19 pandemic, the liberal order and security, and the climate crisis.